‫أثر ‫الإبدا‬ ‫ع ‫الإداري‬ ‫في‬ ‫تحسين‬ ‫الاداء‬ ‫الوظيفي‬ ‫بالمؤسسات‬ ‫االقتصادية‬ ‫‪‬‬‫دراسة ‬‫حالة‬ ‫مؤسسات‬ ‫اتصالات‬ ‫اللاسلكية‬ ‫‪ - ‫عليمة‫ بن‬‫ سالم‬ ‬; روضة ‫ماضي‬‫ ‬ (My University, 2018)
Today innovation plays an important role in the survival of businesses economic. This study aims to identify the reality of innovation and analyze its impact on the performance of human resources in three telecommunications companies, namely: mobilis, djezzy and ooredoo. The study adopted the descriptive analytical approach, using the questionnaire as a means of collecting data. 39 questionnaires out of 42 were analyzed, i.e. 92.85% of the size of the targeted population (42 workers). The study concluded with two important results: the first was to confirm the acceptably the existence of the six internal organizational elements of innovation. THE second shows the existence of a significant relationship between the application of innovation elements and the level of performance of employees within the three companies studied.